The Effect of Work Discipline on Performance with Work Stress as an Intervening Variable in Employees of PT. KIA Plant Karawang - Silitonga, Kris Monica; Mohammad Darul Fadli, Uus; Ery , Rosmawati (Research in Management of Technology and Business, 2024)
The ceramic industry is currently one of the growing and superior industries and is expected to have a significant contribution to the provision of domestic needs and foreign exchange earnings for Indonesia. Challenges arise when employees experience work stress and work discipline in maintaining performance balance so that company goals can be met. This study intends to see how much influence work discipline has on employee performance with work stress as intervening. This research methodology uses a quantitative descriptive approach with which is carried out on employees of PT KIA Plant Karawang with the measuring instrument used in the form of a questionnaire, namely the data obtained consists of employee responses to the questions given. The population of this study amounted to 536 employees and used sampling techniques through the slovin formula with an error rate of 10% so as to get the results of 85 respondents. Data analysis using the Path Analysis Test on SmartPLS4 software . The results of hypothesis testing show that (1) There is a significant positive relationship between Work Discipline and Employee Performance (2) There is a negative and significant relationship between Work Discipline and Work Stress (3) There is a negative and significant relationship between Work Stress and Employee Performance (4) Work Stress as an intervening variable is able to intervene Work Discipline and Employee Performance.